Optimization of Leaching Parameters for Recovery of Tantalum from Waste Tantalum Capacitors - Agrawal M.; Jha R.; Singh K.K.; Singh R. (My University, 2025)
Recycling of tantalum seeking much attention in the recent past, considering its criticality and associated supply risk along with increased demand. Tantalum has become an element of choice in the modern electronic industry due to its superior capacitance in much compact size—a prime requirement of today's technological-driven society. This serves electronic waste as the best secondary resource for tantalum recovery. However, the recovery of tantalum from the capacitor is still developing and facing challenges associated with the separation of tightly covered mold resin containing silica and the dissolution of tantalum in fluoride-free media. In the present investigation, we have developed a hydrometallurgical method to recover tantalum from tantalum capacitors. The tantalum capacitor was first subjected to pre-treatment to separate the encapsulated silica-containing mold resin from the metallic-rich part. After this, the epoxy resin-free tantalum capacitor was leached using double-stage leaching to recover high-purity tantalum in the residue. Various parameters, including temperature, time, acid concentration, and type of acid, were optimized to select the best operating condition for maximum recovery. The obtained tantalum powder was characterized, and it was seen that the proposed two-stage leaching route leads to excellent recovery of tantalum, with the purity of the resultant product being nearly 99.99%. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.